Pengaruh Pendidikan dan Pelatihan Terhadap Peningkatan Kompetensi Pegawai di Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Bekasi - Medline Chatelya; Diana Prihadini; Krishantoro Krishantoro (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The objective of this study is to find out the influence of education and training to increasing of employee competence at Manpower and Human Resource Development Agency (BKPSDM) of Bekasi City. This study used quantitative research method. The data was collected from questionnaire and literature. The population in this study is Government Employees at the Manpower and Human Resource Development Agency (BKPSDM) of Bekasi City. Sampling technique used in this study is total sampling with sample totalled 58 samples. Result of this study identified that education and training at the Manpower and Human Resource Development Agency (BKPSDM) of Bekasi City has significant influence to increasing employees competence.